Antiplatelet aggregation of garlic (Alliun sativum L.) water extract, turmeric (Curcuma domestica Val.) ethanolic extract and its combination to Swiss Webster male mice - Elin Yulinah Iskandar; Joseph I Sigit; Nurul Fitriyani (Indonesian Journal of Pharmacy, 2008)
Antiplatelet aggregation effect of garlic (Allium sativum L.) water extract, turmeric (Curcuma domestica Val.) ethanolic extract and its combination to Swiss Webster mice has been investigated. The test substances given orally during the period of 28 days. Antiplatelet aggregation effect was tested by measuring bleeding time, coagulation time, anddecreasing plasma absorbance to observe platelet aggregation activity before and after addition of ADP as platelet aggregation inducer. Based on the inhibition of plasma abdorbance decrease, turmeric extract at a dose of 100 mg/kg body weight, garlic extract at a dose of 100 mg/kg body weight, combination of turmeric at a dose of 100 mg/kg body weight and garlic extract at a dose of 100 mg/kg body weight as well as combination of turmeric at a dose of 50 mg/kg body weight and garlic extract at a dose of 50 mg/kg body weight showed the effect of platelet aggregation inhibition of 73.67 ± 10.30% (p=0.021); 74.67 ± 25.04% (p=0.018); 77.43 ± 8.09% (p=0.018); and 57.00 ± 23.87% (p=0.047) respectively. The test substances above respectively increased bleeding time of 473.08 ± 56.12% (p<0.000); 427.53 ± 66.89% (p<0.000); 515.73 ± 114.47% (p= 0.001); 481.73 ± 116.51% (p=0.001). Increasing coagulation time only showed by combination of turmeric and garlic extract at a dose of each 100 mg/kg body weight and also of each 50 mg/kg body weight with percentage of 46.67 ± 21.89% (p=0.014) and 40.84 ± 25.80% (p=0.018).Key words : Antiplatelet aggregation, turmeric, garlic, ADP.